Clinical brightening efficacy and safety of Melasolv™ (3, 4, 5‐trimethoxy cinnamate thymol ester, TCTE) in Southeast Asian women. (9th February 2021) - Kim, Seung Hun; Paik, Byung Ryol; Lee, Sung Hoon; Lee, So Mi; Kim, Mi Jin; Kim, Eun Joo; Leow, Chin Yong; Cho, Changhui; Park, Won‐Seok; Suh, Byung‐Fhy
Abstract: Background: Skin darkening because of increased and irregular synthesis of melanin causes melasma, solar lentigo, and freckles. Melasolv™, produced in the early 2000s, shows potent depigmenting effect and has low cytotoxicity. It has been used as a brightening agent in cosmetics for decades. Aims: This study was conducted to investigate whether Melasolv™ is effective for the skin of ASEAN (Southeast Asia) women. Methods: We recruited ASEAN women in Singapore and divided them into two groups (active group vs. placebo group). Melasolv ™ and placebo formulations were applied twice a day for 12 weeks. The changes in the pigmented spots were visually evaluated by an expert and assessed using a spectrophotometer and Mexameter at 0, 4, 8, and 12 weeks. Results: The visual evaluation revealed significant improvements, in both size and color intensity, in the active group compared with those in the placebo group at 12 weeks. In the spectrophotometric evaluation, the L* value of the pigmented spots in the active group was significantly higher than that in the placebo group at 12 weeks. Similar results were obtained in the evaluation using the Mexameter. After 12 weeks, the melanin index of the pigmented spots significantly decreased, and it was significantly higher than that in the placebo group. There was no significant change in the erythema index. In the image analysis, there were no significant differences in skin color brightness and evenness in the active group compared with those in the placebo group. Conclusion: Melasolv ™ can be effective used for skin brightening.